(untitled) (gjstudies, 2022)
This research investigates the nuanced relationship between the adoption of International Financial Reporting Standards (IFRS) and the facilitation of cross-borderinvestment flows, with a specific focus on emerging market economies. While prior literature has predominantly examined the direct effects of IFRS adoption on foreign directinvestment (FDI) volumes, this study introduces a novel, multi-dimensional frameworkthat deconstructs the concept of ’facilitation’ into three distinct channels: informationsymmetry enhancement, regulatory harmonization efficiency, and investor confidencesignaling. We employ a hybrid methodological approach, combining a longitudinalpanel data analysis of 45 emerging economies from 1995 to 2004 with a qualitativecontent analysis of investment committee reports and analyst briefings. This dualmethod design allows us to move beyond aggregate capital flows and examine themechanisms through which reporting standards alter the investment decision-makingcalculus. Our findings reveal a non-linear and conditional relationship. Full IFRSadoption is associated with a significant increase in cross-border portfolio investment,particularly from institutional investors, but shows a weaker, often delayed, correlation with greenfield FDI. Crucially, we identify that the ’facilitation’ effect is heavilycontingent on the pre-existing institutional infrastructure, including the strength ofaudit regimes and enforcement mechanisms. The study’s primary contribution is the’Transparency-Enforcement Nexus’ model, which posits that the benefits of global reporting standards for cross-border investment are fully realized only when high-qualityaccounting transparency is coupled with robust local enforcement. This research challenges the simplistic ’adoption leads to investment’ narrative and provides a moregranular, mechanism-based understanding critical for policymakers in emerging markets